2021
DOI: 10.1212/wnl.0000000000012067
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet, Alzheimer Disease Biomarkers, and Brain Atrophy in Old Age

Abstract: Objective:To determine if following a Mediterranean-like diet (MeDi) relates to cognitive functions and in vivo biomarkers for Alzheimer’s disease (AD), we analyzed cross-sectional data from the German Longitudinal Cognitive Impairment and Dementia StudyMethod:The sample (n=512, mean age: 69.5±5.9 years) included 169 cognitively normal participants and subjects at higher AD risk (53 AD relatives, 209 SCD and 81 MCI). We defined MeDi adherence based on the Food Frequency Questionnaire. Brain volume outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 53 publications
(82 reference statements)
3
73
1
1
Order By: Relevance
“…In a cross-sectional analysis of the National Health and Nutrition Examination Survey (NHANES) survey (2011-2014), Taylor et al found that greater Mediterranean Diet adherence was associated with better cognitive performance among individuals aged 60 years and older (6). Similarly, the German Longitudinal Cognitive Impairment and Dementia Study found that those with greater adherence to the Mediterranean Diet had better memory in older adults (7). Although avocados are not part of a traditional Mediterranean diet, consumption is dramatically increasing worldwide, and their nutrient profile aligns strikingly well with the Mediterranean dietary pattern.…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional analysis of the National Health and Nutrition Examination Survey (NHANES) survey (2011-2014), Taylor et al found that greater Mediterranean Diet adherence was associated with better cognitive performance among individuals aged 60 years and older (6). Similarly, the German Longitudinal Cognitive Impairment and Dementia Study found that those with greater adherence to the Mediterranean Diet had better memory in older adults (7). Although avocados are not part of a traditional Mediterranean diet, consumption is dramatically increasing worldwide, and their nutrient profile aligns strikingly well with the Mediterranean dietary pattern.…”
Section: Introductionmentioning
confidence: 99%
“…According to nationality, fourteen studies [ 1 , 3 , 7 , 8 , 10 , 13 , 17 , 20 , 27 , 33 , 35 , 36 , 38 ] included American participants, four studies [ 9 , 15 , 31 , 32 ] included Australian participants, one study [ 34 ] shows results of Swedish individuals, one study [ 11 ] is based on Brazilian results, other one the participants were German [ 30 ] and only one study was performed in France [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight longitudinal studies [ 1 , 13 , 14 , 16 , 27 , 34 , 37 , 38 ], eleven cross-sectional articles [ 3 , 8 , 10 , 11 , 12 , 17 , 30 , 31 , 32 , 33 , 35 ] and one case-control study nested in a cohort [ 17 ] were included. Also, two studies [ 7 , 36 ] that analyzed its main associations cross-sectional and longitudinally were reviewed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations